Role of diet in fertility: a descriptive cross-sectional study on the knowledge among medical practitioners in South India - Vardhan Yenuganti, Vishnu; Dande Rajasekar, Vedapriya; Nirupama, A. Y. (International Journal Of Community Medicine And Public Health, 2023)
Background: Adherence to healthy diets favouring seafood, poultry, whole grains, fruits and vegetables, are related to better fertility in women and better semen quality in men. Along with pharmaceutical treatment, the role of a proper diet and lifestyle has been highlighted in many diseases like hypertension and diabetes. Likewise, the role of diet in fertility is a less explored area which holds great potential. The first step towards implementation of this fact will be increasing the awareness about the same among healthcare professionals, mainly doctors. Methods: A cross-sectional study including medical practitioners in 3 hospitals each in Tamil Nadu and Kerala. Assuming 50% prevalence and 8% allowable error, sample size was calculated to be 156. Data collection was done using a semi-structured and self-administered questionnaire. Results: Among the total, 80.1% of the medical practitioners responded that diet played an important role in boosting fertility of an individual and 72.1% had faced questions regarding the foods to improve fertility. In terms of knowledge, 28% of the respondents were able to score more than 60 out of a maximum score of 100. Conclusions: Future efforts should concentrate on solidifying emerging evidence and to jointly consider female and male diets along with other interventions for infertility management.